Studies on the variability in reindeer lichens: the evolution of common North American species and thallus resynthesis in Cladonia rangiferina - Athukorala, Sarangi (NRC research Press, 2014)
Cladonia is one of the largest and widely distributed genera of lichen-forming fungi and some form the main winter diet for northern caribou and dominate the northern peatlands. Therefore, they are an ecologically important group of lichens. The ongoing climate change of the northern regions, impose challenges for lichen growth and algal interactions in these species. As in other organisms, genetic variability and phenotypic plasticity in the resynthesis of the lichen thallus will be important for their continued survival. The goal of my thesis is to better understand the variability of the reindeer lichens in an evolutionary and ecological context. Phylogenetic reconstruction (Chapter 2) together with genetic polymorphic studies with RAPD (Chapter 3) showed a lack of monophyly for 12 of 18 species of Cladonia and significant intraspecific genetic variation within the group. Genetic variation in the obligate fungal partner must also rely on the success of the symbiont interaction, which was further studied by resynthesis experiments. In vitro resynthesis experiments of C. rangiferina (Chapter 4) examined recognition- and defense-related genes of the symbionts of C. rangiferina using quantitative Polymerase Chain Reaction (qPCR) (Chapter 5) and suggested that the communication between partners occur and the survival and reestablishment of lichens in nature is affected by the presence of the compatible algal pool. This emphasizes the importance of finding the compatible algal partner for successful lichenization and suggests that parasitism and short-term interaction with incompatible algae may be a strategy allowing the fungus to survive until it finds a compatible algal partner. These studies also make parallels between the lichen symbiosis and plant pathogenic systems and provide molecular evidence for the parasitic nature of the lichen symbiosis. The collapse of the interaction between symbionts of C. rangiferina under varying temperature and pH conditions (Chapter 6) suggests the potential effect of habitat ...